Una lectura estética de la aequalitas en el De musica de Agustín de Hipona - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía Alejandro Korn. Sección de Filosofía Medieval., 2022)
The concept of aequalitas articulates Augustine of Hippo’s analysis in his dialogue De musica. Augustine begins with the technical study of the rhythm of Latin verses in order to organize the metrical feet according to their closeness to equality. Closeness to equality is the criterion of delight, namely, the response of the senses to simple proportions. The rational analysis of the aesthetic experience initiates the ascent of the soul towards God, identified as the foundation of beauty and delight in proportionate and beautiful things. This passage from music theory to the theological philosophy of music articulates an aesthetic theory that addresses aesthetic experience and reflection on this experience. The three moments of the dialogue allow us to understand the concept of aequalitas according to three perspectives: arithmetic, aesthetic and theological. Arithmetic equality is the relationship between two equal quantities. Aesthetic equality is the relationship between the quantities of temporal reality insofar as they are perceived and with respect to their beauty. Finally, theological equality is a supreme equality, divine and without multiplicity.

El concepto de igualdad articula el análisis de Agustín de Hipona en su diálogo De musica. Agustín comienza por el estudio técnico del ritmo de los versos latinos con la función de organizar los pies métricos de acuerdo con su cercanía a la igualdad. La cercanía a la igualdad es el criterio de la delectación, entendida como respuesta de los sentidos ante las proporciones simples. El análisis racional de la experiencia estética da lugar al ascenso del alma hacia Dios, identificado como fundamento de la belleza y de la delectación por las cosas proporcionadas y bellas. Este pasaje de la teoría musical a la filosofía de la música con alcances teológicos articula una teoría estética que aborda la experiencia estética y la reflexión sobre esta experiencia. Sostendremos que los tres momentos del diálogo permiten comprender el concepto de aequalitas de acuerdo con tres perspectivas: aritmética, estética y teológica. La igualdad aritmética es la relación entre dos cantidades iguales. La igualdad estética refiere a las relaciones entre las cantidades de la realidad temporal en tanto que son percibidas y respecto de su belleza. Por último, la igualdad teológica es una igualdad suprema, divina y ajena a la multiplicidad.
An aesthetic approach to the aequalitas in Augustine of Hippo’s De musica
Fil: Szichowski, Patricio Andrés. Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, Argentina.
Keywords: EQUALITY; MOTION; NUMBER; MOTION; IGUALDAD; MOVIMIENTO; NÚMERO; MÚSICA